Breastfeeding Problem in Early Postpartum Period: Mother’s Experiences - Payakkaraung, Sudaporn; Sangperm, Parnnarat; Samart, Chayada (Nursing Science Journal of Thailand, 2016)
Abstract Purpose: To explore breastfeeding problem in postpartum period from mother’s experiences. Design: Exploratory qualitative study. Methods: In-depth interviews were conducted with 28 mothers who were in the early postpartum period (up to two months after delivery) and came for services at lactation clinic. All interviews were tape-recorded and transcribed verbatim. Content analysis was employed for data analysis. Main findings: From mothers’ experiences, breastfeeding problem in early postpartum period could be divided into 5 themes including 1) don’t know, don’t get education; 2) lack of early sucking and continuous stimulate sucking; 3) fail to follow breastfeeding practice at home; 4) feeling of stress and get pressure from others and themselves; and 5) having other problems after discharge from the hospital. Conclusion and recommendations: This study provided a better understanding of breastfeeding problems that mothers faced with in early postpartum period. Supporting the mother to overcome breastfeeding problem in this period should building up the mothers’ confidence to give breastfeeding continuously. ปัญหาการเลี้ยงลูกด้วยนมแม่ระยะแรกหลังคลอด:ประสบการณ์ของมารดา บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาปัญหาการเลี้ยงลูกด้วยนมแม่ในระยะแรกหลังคลอดจากประสบการณ์ของมารดา รูปแบบการวิจัย: การวิจัยเชิงคุณภาพ วิธีดำเนินการวิจัย: สัมภาษณ์เชิงลึกมารดาจำนวน 28 คน ที่อยู่ในระยะแรกหลังคลอด (ภายใน 2 เดือนหลังจากคลอดบุตร) และมารับบริการที่คลินิกเลี้ยงลูกด้วยนมแม่ ทุกการสัมภาษณ์มีการบันทึกเสียงและถอดเทปบันทึกเสียง แล้วจึงวิเคราะห์ข้อมูลด้วยการวิเคราะห์เชิงเนื้อหา ผลการวิจัย: ปัญหาการเลี้ยงลูกด้วยนมแม่ในระยะแรกหลังคลอดจากประสบการณ์ของมารดา แบ่งได้เป็น 5 ประเด็นหลัก คือ 1) ไม่รู้ ไม่ได้รับการสอน 2) ขาดการเริ่มดูดเร็วและไม่ได้ดูดกระตุ้นอย่างต่อเนื่อง 3) เมื่อกลับบ้าน ได้พยายามทำตามที่ได้รับการสอน แต่ทำไม่สำเร็จ 4) มีความเครียดและรู้สึกกดดันจากตนเอง และคนรอบข้าง และ 5) มีปัญหาแทรกซ้อนที่พบในภายหลังเมื่อออกจากโรงพยาบาล สรุป และข้อเสนอแนะ: การศึกษานี้ช่วยเพิ่มความเข้าใจปัญหาการเลี้ยงลูกด้วยนมแม่ที่มารดาต้องเผชิญในระยะแรกหลังคลอด การสนับสนุนมารดาในการเผชิญปัญหาในระยะนี้จะช่วยให้มารดามีความมั่นใจและสามารถเลี้ยงลูกด้วยนมแม่ได้อย่างต่อเนื่อง คำสำคัญ: การเลี้ยงลูกด้วยนมแม่ ประสบการณ์ของมารดา ระยะแรกหลังคลอด